2020
DOI: 10.1007/s40032-020-00554-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Beryl Reinforcement in Aluminum 2024 on Mechanical Properties

Abstract: The current technology landscape lacks a foundational AI model for solving process engineering calculations. In this work, we introduce a novel autonomous agent framework leveraging Retrieval-Augmented Instruction-Tuning (RAIT) to enhance open, customizable small code language models (SLMs) for these calculations. By combining instructiontuned code SLMs with Retrieval-Augmented Code Generation (RACG) using external tools, the agent generates, debugs, and optimizes code from natural language specifications. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The Devasthal observatory is situated at an altitude of ∼2450m, with longitude 79 • 41 ′ 04 ′′ East and latitude +29 • 21 ′ 40 ′′ (c.f. Sagar et al 2011Sagar et al , 2012. It is important to highlight that in view of the site advantages, apart from the upcoming 4-m ILMT, the other existing astronomical observing facilities at Devasthal are the 1.3-m DFOT 2 and 3.6-m DOT 3 .…”
Section: The Ilmt Projectmentioning
confidence: 99%
“…The Devasthal observatory is situated at an altitude of ∼2450m, with longitude 79 • 41 ′ 04 ′′ East and latitude +29 • 21 ′ 40 ′′ (c.f. Sagar et al 2011Sagar et al , 2012. It is important to highlight that in view of the site advantages, apart from the upcoming 4-m ILMT, the other existing astronomical observing facilities at Devasthal are the 1.3-m DFOT 2 and 3.6-m DOT 3 .…”
Section: The Ilmt Projectmentioning
confidence: 99%
“…It was observed that the ultimate tensile strength of the aluminium alloy 2024/beryl composites were significantly more than the as‐cast aluminium alloy 2024 material. Also, the density of the composites declined with a rise in weight fraction of beryl, primarily due to the increase in the porosity of these composites [20].…”
Section: Introductionmentioning
confidence: 99%
“…Fiber-reinforced polymer and metal laminated structures are widely applied in fields such as aerospace, aviation, and military, due to the excellent material properties [1][2][3]. In practical applications, it is often necessary to process fiber-reinforced polymer and metal laminated structures to meet the requirements of use.…”
Section: Introductionmentioning
confidence: 99%